The relationships between personal needs and subjective career success: Mediating effects of networking behaviors - Kang, SeungHye; Tak, Jinkook (Korean Journal of Industrial and Organizational Psychology, 2014)
The purpose of this study was to examine the mediating effects of networking behaviors on the relationships between individual needs and subjective career success. Data were obtained from 197 employees in various organizations who have been employed for more than two years. Structural equation analyses were conducted to test hypotheses. Results showed that achievement needs affected task networking behavior and affiliation needs affected affiliative networking behavior. Only task networking behavior affected subjective career success. Thus, task networking behavior mediated the relationship between achievement needs and subjective career success. Finally implications, limitations, and future studies were discussed.